The impact of administrative creativity in consolidating organizational culture in private schools in the Holy Capital - Turkstany, Ghaliah Habibullah (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to measure the impact of administrative creativity on the consolidation of organizational culture in private schools, from the point of view of employees and leaders in private schools in the Holy Capital. The study used the descriptive analytical method, and the tool was the questionnaire; it was distributed to a stratified sample of (87) From school leaders and administrators in private schools in the Holy Capital,  The study found that managerial creativity had a total average (3.94 out of 5), and at the level of its four dimensions, encouraging creativity received the highest average (4.06), then originality (3.96), flexibility (3.93), and finally problem sensitivity (3.79), all with a verbal grade (large), while the organizational culture axis obtained a total average (3.77 out of 5), and the dimensions were arranged as follows (rituals, 3.94; values, 3.87; standards, 3.85 (all with a grade of (large). Finally, communications with an average of (3.40) and an estimate (medium), and the axis of administrative leadership obtained a total average of (3.25 out of 5) and an estimate (average), and the results showed a positive impact of administrative creativity on the consolidation of organizational culture in private schools in the Holy Capital, amounting to (3.94), and that there is a positive impact of administrative leadership on organizational culture, as well as there are statistically significant differences between the averages of the responses of the study sample at the level of (α≤0.05) On the impact of administrative creativity on the organizational culture in private schools attributed to variables (gender; in favor of the female - age in favor of (41_50) years - qualification in favor of the university - job title in favor of administrative - years of experience in favor of 10 years or more), based on the results, the researcher recommended the need to form open channels of communication, for greater acceptance of new opinions, and the need for a special administration interested in creative processes and the participation of tasks, and the establishment of a club that brings together the administrations of private schools. In addition to proposals for complementary studies on the subject.
Keywords: impact; administrative creativity; organizational culture; private schools